People-first PPPs for services: Operational needs - Chevalier, Doris (ITM web of conferences, 2023)
The public-private partnership is a public procurement tool that accelerates the implementation of major projects and contributes to the recovery of the economy. Based on precise and regulated principles, it is a complex tool that requires significant expertise to use. As such, digitalization can facilitate its use at each stage of its realization.